Application of RELUX simulation to investigate energy saving potential from daylighting in a new educational building in UK - Yu, Xu; Su, Yuehong; Chen, Xin (Elsevier, 2014)
Daylighting is a renewable energy solution for illumination and visual comfort in buildings. Daylighting performance and its induced energy saving largely depends on various factors, including room geometry, window-to-wall ratio, window transmittance, surface reflectance of construction and surrounding obstructers, artificial lighting array, its daylight-related control strategies and so forth. During the last few decades, lighting simulation tools developed quickly to provide researchers and architects a faster and reliable ways to simulate complex lighting environment. The aim of this paper is to deal with a quantitative analysis of annual energy saving potential from daylighting in a real building using various methods. A case study of a newly constructed educational atrium building, Engineering and Science Learning Centre (ESLC) in the University of Nottingham, UK, is presented. Computational analysis using validated lighting simulation tool RELUX will be conducted to simulate the daylighting performance in the selected rooms. Particularly, an economical measurement of window transmittance and interior surface reflectance will be conducted, and the measured results will be input into the simulation software to increase the accuracy of simulation results. The annual energy saving potential in artificial lighting from daylighting is determined by European Standard EN15193 and also estimated using static climate-based Daylight Factor (DF) method and dynamic climate-based Daylight Coefficient (DC) methods.